Identification and Continuity of Zie’s Batik Motifs in the Village of Malon Gunungpati Semarang City - Abas Karend, Khanza Azizah; Na’am, Muh Fakhrihun (Journal of Vocational and Career Education, 2020)
Zie Batik in the Village of Malon Gunungpati, Semarang City has more characteristics namely the batik motifs that are produced. The batik motifs in Zie Batik were identified based on the research focus. The purpose of this study is to describe the identification of the motifs and to determine the continuity of the Zie batik motifs. The research method uses qualitative research methods. This research data collection technique with observation, interviews, and documentation. Data analysis using data reduction, data presentation, and drawing conclusions. This study uses source triangulation techniques to ensure data validity. The results showed that the motifs that were produced continuously were batik motifs with icons in the city of Semarang for combination batik types, and written batik, namely legendary motifs. Batik Zie in Kampung Malon originates from the idea of the surrounding nature by raising local wisdom. The batik motifs that have been produced continuously today are the Semarang icon motifs and legends. It is necessary to develop written batik motifs based on the idea of Gunungpati, namely the legend of Nyi Sekar on the development of combined batik and stamped batik developed with the source of the Semarang City icon idea, namely the Jatibarang Reservoir, Icon Durian Monti (Montong Gunungpati).